On-chip signaling techniques for high-speed Serdes transceivers - Tadros, Ramy Nagy (AUC Knowledge Fountain, 2015)
The general goal of the VLSI technology is to produce very fast chips with very low power consumption. The technology scaling along with increasing the working frequency had been the perfect solution, which enabled the evolution of electronic devices in the 20th century. However, in deep sub-micron technologies, the on-chip power density limited the continuous increment in frequency, which led to another trend for designing higher performance chips without increasing the working speed. Parallelism was the optimum solution, and the VLSI manufacturers began the era of multi-core chips. These multi-core chips require a full inter-core network for the required communication. These on-chip links were conventionally parallel. However, due to reverse scaling in modern technologies, parallel signaling is becoming a burden due to the very large area of needed interconnects. Also, due to the very high power due to the tremendous number of repeaters, in addition to cross talk issues. As a solution, on-chip serial communication was suggested. It will solve all the previous issues, but it will require very high speed circuits to achieve the same data rates. This thesis presents two full SerDes transceiver designs for on-chip high speed serial communication. Both designs use long lossy on-chip differential interconnects with capacitive termination. The first design uses a 3-level self-timed signaling technique. This signaling technique is totally jitter-insensitive, since both of the data and clock are extracted at the receiver from the same signal. A new encoding and driving technique is designed to enable the transmitter to work at a frequency equal to the data rate, which is half of the frequency of the previous designs, along with achieving the same data rate. Also, this design generates the third voltage level without the need of an external supply. This design is very tolerant to any possible variations, such as PVT variations or the input clock's duty cycle variations. This transceiver is prepared for tape-out in UMC 0.13ÃŽÂ¼m CMOS technology in June 2014. The second design uses a new 3-level signaling technique; the proposed technique uses a frequency of only half the data rate, which totally relaxes the full transceiver design. The new technique is also self-timed enabling the extraction of both the data, and the clock from the same signal. New encoders and decoders are designed, and a new architecture for a 3-level inverter is presented. This transceiver achieves very high data rates. This new design is expected to be taped-out using the GF 65nm CMOS technology in August 2014.